GEOTECHNICAL CHARACTERIZATION OF SOFT CLAY ALONG A HIGHWAY IN THE RED RIVER DELTA - P. H. Giao; D. H. Hien (Lowland Technology International, 2007)
The Red River Delta (RRD) consists mostly of Pleistocene to Holocene deposits, including soft clays. Besides environmental hazards such as flood, storm, coastal erosion, saltwater instruction and contamination of ground water, the wide distribution of soft clay has caused obvious geotechnical difficulties for infrastructure development projects. It is observed that the economic growth of this booming region of Vietnam goes at a faster rate than that of the infrastructure development and the latter has not yet been supported by a modern geotechnical investigation practice. Data analysis and soil characterization become even more difficult for a long linear infrastructure like a road or highway, whose route runs over different soil types. This study deals with a comprehensive geotechnical characterization of soft soils underlying the national highway No. 18 (NH18) that has often had problems of differential settlements or other construction damages. Besides the common approach of lumping testing data in the averaged graphs and tables, visualizations were made to assist in characterization of the soil layers. A number of empirical correlative relationships were deduced for various geotechnical parameters, especially the undrained shear strength and the cone tip resistance.